Adaptive Behavior in Stroke Survivors: A Concept Analysis - Hyunsuk Choi; Ancho Lim; Youngshin Song (Elsevier, 2022)
SUMMARY: Purpose: This study aims to explore a clear and evidence-based definition of adaptive behavior in stroke survivors and establish the antecedents, attributes, consequences, and empirical referents of the concept. Methods: The concept analysis was performed using the Walker and Avant method as a framework. Data from 90 publications were collected using various databases (PubMed, EMBASE, CINAHL, RISS, and KISS) and applied in the analysis. Results: Adaptive behavior in stroke survivors was defined according to four attributes: realizing change, taking an optimistic view, restructuring daily activities to suit oneself, and carrying out one's own daily life. The conceptual structure of their adaptive behavior comprised stroke onset, functional changes, and emotional liability as antecedents and autonomy, family equilibrium, and quality of life as consequences. Conclusions: Clarifying the concept of adaptive behavior in stroke survivors provides an understanding of the underlying attributes of this concept. Furthermore, it will facilitate the development of scales to measure the concept and the application of a theory-based intervention program that can improve adaptive behavior.